2019
DOI: 10.31729/jnma.4431
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Perinatal Deaths in A Tertiary Care Hospital of Nepal

Abstract: Introduction: Perinatal mortality indicates quality of maternal and neonatal care and is high inNepal. This study was conducted to find out the prevalence of perinatal deaths in a tertiary carecenter. Methods: This descriptive cross-sectional study was conducted from July 2017 to June 2018 at KISTMedical College and Teaching Hospital. Details of each perinatal death were filled in predesignedproforma from hospital in-patient records within 24 hours of perinatal death. The total of 1088 caseswere selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
1
6
2
Order By: Relevance
“…The contrast finding was found in a study conducted in one Medical College and Teaching Hospital, Kathmandu that is 81.25% were preterm births while 18.75% were term. 2 Another study conducted by Rai et al showed perinatal deaths more at gestational age <34 weeks and at >40 weeks, 9 which has different findings with this study. About the sex of the baby; 102 (54.5%) were male and 85 (45.5%) were female.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…The contrast finding was found in a study conducted in one Medical College and Teaching Hospital, Kathmandu that is 81.25% were preterm births while 18.75% were term. 2 Another study conducted by Rai et al showed perinatal deaths more at gestational age <34 weeks and at >40 weeks, 9 which has different findings with this study. About the sex of the baby; 102 (54.5%) were male and 85 (45.5%) were female.…”
Section: Discussioncontrasting
confidence: 72%
“…This research was conducted after getting ethical approval from the institutional review committee (2076/2077/05) of the Karnali Academy of Health Sciences. The sample size was calculated using the following formula: n= Z 2 x p x q / e 2 = (1.96) 2 x 0.5 x (1-0.5) / (0.02) 2 = 2401 Where, n= minimum required sample size Z= 1.96 at 95% Confidence Interval (CI) p= 50%, for maximum sample size calculation q= 1-p e= margin of error, 5%…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated the PMR of 16.24 per 1000 births with a Stillbirth rate of 9.65 per 1000 births and an Early neonatal mortality rate of 6.49 per 1000 live births during the period 2018-19 at KISTMCTH.Two previous studies of perinatal mortality rate at KISTMCTH from 2016-17 and 2017-18 showed a perinatal mortality rate of 16.27 and 14.53/1000 total births respectively. 7,8 The perinatal mortality rate has been static over the last 3 years at KISTMCTH. However, the perinatal mortality rate was 12.3 per thousand birth in the study conducted at Bharatpur Hospital, Nepal with the increasing trend of PMR over the two years.…”
Section: Discussionmentioning
confidence: 99%
“…The department of Family Health Division of the Ministry of Health and Population of Nepal investigates perinatal deaths under the program, Maternal and Perinatal Death Surveillance and Response (MPDSR) System [ 6 ]. Perinatal mortality is significantly contributed by stillbirths and prematurity in Nepal, and it can be minimized by provisions for antenatal surveillance and monitoring, timely referral of high-risk pregnancies and good neonatal care to preterm neonates [ 7 ].…”
Section: Introductionmentioning
confidence: 99%